Desarrollo Socio-Emocional como un estilo de aprendizaje áulico - Navarrete Socasi, Sonia Alexandra (2022)
The objective of this research project in known how socio-emotional development affects children learning at Initial Education, trying to identify socio-emotional development incidence at learning, to improve teaching- learning of Educational Unit "Juan Abel Echeverría" children of Initial Education sublevel II, at Cotopaxi Province, Latacunga Canton, Eloy Alfaro Parish. The applied methodology is qualitative, where a bibliographical investigation was carried out to provide significant information from various authors, different data collection techniques were used, such as interview, focus group and observation, which provided different contributions and opinions, to obtain an analysis and reflection, it is thus lack of direct contact between classmates - teachers with leads to negative responses of frustration, anxiety, stress, shyness and anger, being one of the main factors that affects learning, the variation of emotions and non-concentration are present behind a screen influencing the development of abilities and skills that are potentiated in early childhood, therefore it is concluded that socio-emotional children development allows self-confidence to establish communication and a relationship with people around, today infants are faced to various emotions that cause different reactions, therefore it mostly affects learning, is essential to motivate, rebuild their confidence and foster an approach taking into account that the process occurs at any time, circumstance and place, motivating to maintain a coexistence and trust between the environment by abilities and skills acquisition that allows getting a comprehensive education that accompanies good emotional, empathic and social interaction state.